Intracellular Ca2+ Signaling and Calcium Release-Activated Calcium Modulator ORAI1 Are Associated With CD4+ T Lymphocytes in Dairy Cows - Li, Ming; Zhang, Bingbing; Yin, Yufeng; Wen, Jianan; Wang, Jingjing; He, Yuxin; Jiang, Qianming; Loor, Juan J.; Wang, Shuang; Yang, Wei; Xu, Chuang (Frontiers in Immunology, 2022)
The nutritional status of dairy cows and the metabolism of specific nutrients are critical regulators of immune cell function. Around the time of parturition, mobilization of body lipid and muscle helps compensate for the decrease in nutrient intake and the increased requirements of the mammary gland for lactation. An end-result of these processes is the marked increase in circulating concentrations of fatty acids (FA), which are a major risk factor for immune dysfunction. In food animal species such as dairy cows, any disturbance in nutritional or immunological homeostasis leads to deleterious feedback loops that can further risk health, efficiency of nutrient use, and compromise availability of safe and nutritious dairy foods for humans. Despite substantial progress with respect to regulation of innate immunity, such knowledge for adaptive immunity is scarce. To help bridge this gap in knowledge, we sought to study the role of calcium release-activated calcium modulator ORAI1 activation in T cells systemic immune function in vivo. CD4+ T cells were isolated from peripheral blood of dairy cows diagnosed as healthy or with ketosis, a common metabolic disorder of FA metabolism. Results revealed that levels of intracellular Ca2+ and reactive oxygen species (ROS) along with the abundance of store-operated Ca2+ entry (SOCE) moiety increased during ketosis. Further, plasma concentrations of inflammatory cytokines were elevated, the balance of Th17/Treg cells was disrupted, mitochondrial function impaired, and the abundance of mitophagy-related proteins in CD4+ T cells altered during ketosis. Molecular characterization of the direct effects of FA was evaluated in CD4+ T cells isolated from the spleen. Enhanced supply of FA increased intracellular Ca2+ and ROS concentrations, upregulated the abundance of proteins associated with mitochondrial dynamics and ORAI1. Intermediates of mitophagy accumulated and the balance of Th17/Treg cells also was affected by the supply of FA. These negative effects were attenuated by silencing or inhibition of ORAI1 in CD4+ T cells. Together, data indicated that physiological states that lead to increases in systemic concentrations of FA could impact negatively adaptive immunity through ORAI1 regulate intracellular Ca2+, ROS balance, and increases content of Th17 cells.